Pengaruh Asimetri Informasi, Moralitas Individu Dan Pengendalian Internal Terhadap Kecenderungan Kecurangan Akuntansi - Komala, Rina; Piturungsih, Endar; Firmansyah, M. (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This study aims to analyze the effect of information asymmetry, individual morality and internal control on the tendency of accounting fraud on the use of village funds in Utan District, Sumbawa Regency. The number of respondents used in this study were 44 people. Data collection is done by survey method with data collection techniques using questionnaires. The results of the study is the information asymmetry variable has a positive influence on the tendency of accounting fraud; individual morality variable has a negative influence on the tendency of accounting fraud; and internal control variable has a negative influence on the tendency of accounting fraud. Keywords : Asymmetry; Morality; Control; Accounting Fraud.